Disease course of neurofibromatosis type 2: a 30-year follow-up study of 353 patients seen at a single institution. Issue 7 (18th December 2020) - Forde, Claire; King, Andrew T; Rutherford, Scott A; Hammerbeck-Ward, Charlotte; Lloyd, Simon K; Freeman, Simon R; Pathmanaban, Omar N; Stapleton, Emma; Thomas, Owen M; Laitt, Roger D; Stivaros, Stavros; Kilday, John-Paul; et al.
Abstract: Background: Limited data exist on the disease course of neurofibromatosis type 2 (NF2) to guide clinical trial design. Methods: A prospective database of patients meeting NF2 diagnostic criteria, reviewed between 1990 and 2020, was evaluated. Follow-up to first vestibular schwannoma (VS) intervention and death was assessed by univariate analysis and stratified by age at onset, era referred, and inheritance type. Interventions for NF2-related tumors were assessed. Cox regression was performed to determine the relationship between individual factors from time of diagnosis to NF2-related death. Results: Three hundred and fifty-three patients were evaluated. During 4643.1 follow-up years from diagnosis to censoring, 60 patients (17.0%) died. The annual mean number of patients undergoing VS surgery or radiotherapy declined, from 4.66 and 1.65, respectively, per 100 NF2 patients in 1990-1999 to 2.11 and 1.01 in 2010-2020, as the number receiving bevacizumab increased (2.51 per 100 NF2 patients in 2010-2020). Five patients stopped bevacizumab to remove growing meningioma or spinal schwannoma. 153/353 (43.3%) had at least one neurosurgical intervention/radiation treatment within 5 years of diagnosis. Patients asymptomatic at diagnosis had longer time to intervention and better survival compared to those presenting with symptoms. Those symptomatically presenting <16 and >40 years had poorer overall survival than those presenting at 26-39 years ( P = .03 and P = .02, respectively) but those presenting between 16 and 39 had shorter time to VS intervention. Individuals with de novo constitutional variants had worse survival than those with de novo mosaic or inherited disease ( P = .004). Conclusion: Understanding disease course improves prognostication, allowing for better-informed decisions about care.